When ?together? means ?too close? agency motives and relationship functioning in coresident and living-apart-together couples. [article]. - Hagemeyer, Birk; Schonbrodt, Felix D.
The present research addresses the interplay between agency motives and objective dyadic closeness with regard to the functioning of intimate couple relationships. Applying a Person × Situation approach, we hypothesized (a) that partners' implicit and explicit agency motives predict their selection of dyadic living arrangements characterized by high or low objective closeness (coresidence or living-apart-together), (b) that agency motives have more negative effects on relationship functioning in coresident couples, (c) that agency motives predict agentic motivational states in coresident couples, and (d) that agentic states predict day-to-day changes in relationship satisfaction under conditions of high objective closeness. We found support for these between- and within-couple hypotheses in cross-sectional and prospective analyses of an age-heterogeneous sample of 548 heterosexual couples, and in a 2-week diary study with a subsample of 106 couples. Most notably, agentic motive dispositions and motivational states related to relationship functioning more negatively under conditions of high objective closeness. The overall positive effect of objective closeness on relationship functioning was diminished by strong agentic motivation. Perspectives for future research on agency motives in couple relationships are discussed.-- (from the authors)